2016
DOI: 10.20471/acc.2016.55.02.06
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Anthropometric Measurements of Obesity in Prediction of Microvascular Complications in Obese Type 2 Diabetic Patients

Abstract: SUMMARY -Waist circumference (WC), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR) are superior to body mass index (BMI) in predicting type 2 diabetes mellitus (T2DM) development. Th e aim of this study was to investigate the predictive power of BMI, WC, WHR and WHtR for microvascular (chronic kidney disease (CKD), retinopathy and peripheral neuropathy) prevalence in obese (BMI ≥35 kg/m 2 ) T2DM patients. Th is cross-sectional study included 125 T2DM patients of both genders. Th e validity of each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
(51 reference statements)
0
13
0
1
Order By: Relevance
“…Acute microangiopathy is also known as acute systemic microangiopathy, such as shock and DIC [9]; however, the most typical diabetes-induced microangiopathy is chronic microangiopathy [10]. Numerous studies have found that endothelial cells play key roles in the pathogenesis of diabetic microangiopathy, and significant changes occur in the cell structure and function [11]. In diabetic retinopathy and glomerular lesions, vascular endothelial cells are damaged, which destroy the blood-retinal and blood-glomerular barriers, thickens the stroma, and induces fibrotic changes, eventually leading to retinal detachment or glomerular barrier dysfunction [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Acute microangiopathy is also known as acute systemic microangiopathy, such as shock and DIC [9]; however, the most typical diabetes-induced microangiopathy is chronic microangiopathy [10]. Numerous studies have found that endothelial cells play key roles in the pathogenesis of diabetic microangiopathy, and significant changes occur in the cell structure and function [11]. In diabetic retinopathy and glomerular lesions, vascular endothelial cells are damaged, which destroy the blood-retinal and blood-glomerular barriers, thickens the stroma, and induces fibrotic changes, eventually leading to retinal detachment or glomerular barrier dysfunction [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Th e results on the mean waist circumference in patients (100.43±13.88 cm for female and 105.07±8.98 cm for male patients) were higher than the reference data from the literature, which are 92±13 cm 22 and 88±12 cm 23 . Th e greater the waist circumference, the greater is the risk of chronic disease development and cardiovascular events, with the accumulation of fat around the waist being a predictor of NAFLD development [25][26][27] . Th e results on BMI in this research are closest to the results obtained in Italy 22 , while the mean waist circumference was >10% greater than in the same group of Italian subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin was measured by chemiluminescent immunometric assay (Immulite 2000, Siemens, Munich, Germany). Homeostasis assessment of insulin resistance (HOMA-IR) and eGFR were calculated as described in detail elsewhere ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%